Late gadolinium enhancement characteristics in giant cell myocarditis - Yang, Shujuan (ESC Heart Fail, 2021)
AIMS: This study aims to demonstrate the characteristics of late gadolinium enhancement (LGE) assessed by cardiovascular magnetic resonance (CMR) imaging in patients with giant cell myocarditis (GCM). METHODS AND RESULTS: Six patients histologically diagnosed with GCM were retrospectively recruited in this study. All of them underwent CMR during hospitalization. The distribution and extent of LGE were assessed on both ventricles, and the AHA‐17 segment model was used for left ventricular (LV) analysis. Nine case reports with CMR in GCM were reviewed and summarized to investigate the features of LGE further. LGE was detected on both ventricular walls in all subjects. For a detailed analysis of LGE in the LV, the extent ranged from 21.6% to 56%. Among 70 segments (68.6%) involved by LGE, the subendocardial LGE was the most common pattern (46/102, including 24 segments located in the right‐sided septum), followed by the subepicardial pattern (23/102). The right‐sided septum, the subepicardial anterior wall, and the subendocardial right ventricular (RV) wall were observed in all subjects. To summarize the results of the present study with these case reports, the three most common patterns of LGE are the right‐sided septum (73%), the subepicardial anterior wall (60%), and the subendocardial RV wall (53%). CONCLUSIONS: Extensive LGE seems to be common in GCM, affecting both LV and RV walls. Apart from subepicardial LGE, subendocardial LGE, which was used to be implicated in ischaemic disease, was frequently presented in GCM. The right‐sided subendocardial septum, the subepicardial anterior wall, and the subendocardial RV wall might be the vulnerable areas of LGE in GCM.